Investigation of the efficiency of some fungicides and disinfectants applied in Agaricus bisporus cultivation - Misz, András; Allaga, Henrietta; Büchner, Rita; Varga, András; Bakos-Barczi, Nóra; Bajzát, Judit; Kredics, László; Csutorás, Csaba; Vágvölgyi, Csaba (Acta Biologica Szegediensis, 2023)
Pathogenic moulds (e.g., Trichoderma, Hypomyces, and Lecanicillium) cause huge problems in industrial scale production of Agaricus bisporus. It is important to choose the right control strategy, either chemical or biocontrol-based, to prevent substantial economic losses. The present study was carried out to reveal the in vitro efficacy of some fungicides and disinfectants against causative agents of wet bubble (Hypomyces perniciosus), dry bubble (Lecanicillium fungicola var. fungicola), cobweb disease (Hypomyces odoratus), and green mould (e.g., Trichoderma aggressivum f. aggressivum, T. aggressivum f. europaeum, T. harzianum), the four most devastating fungal infections in mushroom production. Prochloraz was efficient against Trichoderma and H. perniciosus isolates. Metrafenone did not cause complete inhibition for any of the isolates even at the highest concentration (5%) tested. In both cases Lecanicillium isolates displayed the lowest growth rate inhibition. Concerning the tested disinfectants, treatment with Sekusept Aktiv resulted in complete growth inhibition for all isolates in the concentration range of 1.25-5%. Terralin Protect, Disinflex and Formalin were also effective, except against the tested isolates of T. agressivum f. agressivum which proved to be the most resistant.